Експериментальне визначення трибоелектричного потенціалу в мережевих неекранованих та екранованих кабелях - Беспрозванных, А.В.; Бойко, А.М. (Електротехніка і електромеханіка, 2012)
At application of both unshelded and shelded twisted pairs of
structured cable networks, additional noise is generated directly in
the cables structures with different materials. It is caused by a
triboelectric effect. Values of the triboelectric potential in unshielded
and shielded 5†-category cable samples are experimentally
determined. It is revealed that there is a constant component.